St. George Tucker papers - Tucker, St. George, 1752-1827.
Chiefly letters (1788-1801) to Tucker from his stepson, John Randolph of Roanoke (1773-1833), relating to personal and family matters. Other correspondents include Bishop James Madison, James Monroe, and John Page. Topics include the Revolution and politics in Virginia. Also includes two copies of a poem (1818 March 20) entitled "To the Memory of General Washington."
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Jurist and army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Madison, James, -- 1749-1812 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Page, John, -- 1744-1808 -- Correspondence; Randolph, John, -- 1773-1833 -- Correspondence; Washington, George, -- 1732-1799 -- Poetry; Virginia -- Politics and government -- 1775-1865.; Virginia -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.; Army officers; Jurists